Fluorescent Graphitic Carbon Nitride (g-C3N4)-Embedded Hyaluronic Acid Microgel Composites for Bioimaging and Cancer-Cell Targetability as Viable Theragnostic - Selin S. Suner; Mehtap Sahiner; Sahin Demirci; Evrim Umut; Nurettin Sahiner (MDPI AG, 2024)
Fluorescent graphitic carbon nitride (g-C3N4) doped with various heteroatoms, such as B, P, and S, named Bg-C3N4, Pg-C3N4, and Sg-C3N4, were synthesized with variable band-gap values as diagnostic materials. Furthermore, they were embedded within hyaluronic acid (HA) microgels as g-C3N4@HA microgel composites. The g-C3N4@HA microgels had a 0.5-20 μm size range that is suitable for intravenous administration. Bare g-C3N4 showed excellent fluorescence ability with 360 nm excitation wavelength and 410-460 emission wavelengths for possible cell imaging application of g-C3N4@HA microgel composites as diagnostic agents. The g-C3N4@HA-based microgels were non-hemolytic, and no clotting effects on blood cells or cell toxicity on fibroblasts were observed at 1000 μg/mL concentration. In addition, approximately 70% cell viability for SKMEL-30 melanoma cells was seen with Sg-C3N4 and its HA microgel composites. The prepared g-C3N4@HA and Sg-C3N4@HA microgels were used in cell imaging because of their excellent penetration capability for healthy fibroblasts. Furthermore, g-C3N4-based materials did not interact with malignant cells, but their HA microgel composites had significant penetration capability linked to the binding function of HA with the cancerous cells. Flow cytometry analysis revealed that g-C3N4 and g-C3N4@HA microgel composites did not interfere with the viability of healthy fibroblast cells and provided fluorescence imaging without any staining while significantly decreasing the viability of cancerous cells. Overall, heteroatom-doped g-C3N4@HA microgel composites, especially Sg-C3N4@HA microgels, can be safely used as multifunctional theragnostic agents for both diagnostic as well as target and treatment purposes in cancer therapy because of their fluorescent nature.